Identifying patient-important outcomes in medication-assisted treatment for opioid use disorder patients: a systematic review protocol. Issue 12 (4th December 2018) - Sanger, Nitika; Shahid, Hamnah; Dennis, Brittany B; Hudson, Jackie; Marsh, David; Sanger, Stephanie; Worster, Andrew; Teed, Rand; Rieb, Launette; Tugwell, Peter; Hutton, Brian; Shea, Beverley; et al.
Abstract : Introduction: Illicit opioid use has become a national crisis in Canada, with over 65 000 people seeking treatment for opioid use disorder (OUD) in Ontario and British Columbia alone. Medication-assisted treatment (MAT) is a common treatment for OUD. There is substantial variability in treatment outcomes used to evaluate effectiveness of MAT, making it difficult to establish clinically and scientifically relevant treatment effect. Furthermore, patients are often excluded from the process of determining these outcomes. The primary objective of this review is to examine outcomes currently used to measure MAT effectiveness and to identify patient-relevant outcomes to enhance effectiveness of treatment options. This review refers to patient-important outcomes as those outcomes patients consider important to or markers of treatment success. Methods and analysis: MEDLINE, EMBASE, PsycINFO, Cumulative Index to Nursing and Allied Health Literature, Web of Science, Cochrane Library, Cochrane Clinical Trials Registry, National Institutes for Health Clinical Trials Registry and WHO International Clinical Trials Registry Platform databases will be searched. We will search databases from inception to the date the search is ran. Studies of interest include those evaluating the effectiveness of MAT for patients with OUD, with or without consultation with patients regarding what they consider to be important as an indicator of treatment success. Results will be analysed using thematic analysis and qualitative analysis where possible. This will result in comprehensive synthesis of all outcomes and measures found related to OUD treatment effectiveness. Ethics and dissemination: We are collaborating with Canadian Addiction Treatment Centres which provide MAT to patients with OUD who will participate in disseminating study results. Dissemination strategies will involve sharing study results through workshops, presentations, peer-reviewed publications, study reports, community presentations and resources in primary care settings. PROSPERO registration number: CRD42018095553.